2001
DOI: 10.1034/j.1601-0825.2001.0070304.x
|View full text |Cite
|
Sign up to set email alerts
|

Benign fibro-osseous lesions of the jaw bones in Jamaica: analysis of 32 cases

Abstract: These lesions are more common in females, furthermore it is suggested that the inconsistent age at presentation for some of these lesions may be peculiar to Jamaica, and may be due to delay in reporting a lesion by the patient, as routine dental examination is not a common practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
6

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 0 publications
2
12
0
6
Order By: Relevance
“…Among them, the four important studies were carried out by Alsharif et al ., on Chinese population,[6] Ogunsalu et al ., on Jamican population,[7] Langdon et al ., on OFs,[4] and Bustamante et al ., has compared clinical and pathologic features of 11 FOL of maxillas. [8] [Table 4].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the four important studies were carried out by Alsharif et al ., on Chinese population,[6] Ogunsalu et al ., on Jamican population,[7] Langdon et al ., on OFs,[4] and Bustamante et al ., has compared clinical and pathologic features of 11 FOL of maxillas. [8] [Table 4].…”
Section: Discussionmentioning
confidence: 99%
“…Ogunsalu et al. (26) found that in Jamaica the most common types of fibro‐osseous lesions of the jaws were fibrous dysplasia (51.7%), followed by ossifying fibroma (34.5%). In contrast, in this study ossifying fibroma was the most common (50.8%), followed by fibrous dysplasia (42.6%).…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of reports on geographic or racial variation in the relative frequency of fibro‐osseous jaw lesions in the English‐language literature, other than that by Ogunsalu et al. (26). To our knowledge, there are no previously published reports on the relative frequencies and the clinicopathologic features of fibro‐osseous jaw lesions in Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Malignant transformation is rare, and is usually precipitated by radiation therapy. 6,8 The diagnosis of fibrous dysplasia can be made by radiologic imaging and confirmed by bone biopsies. Computed tomography (CT) and magnetic resonance imaging are useful for evaluating the soft tissue components and the entire extent of a lesion.…”
Section: Introductionmentioning
confidence: 99%